Differences in Eating Behavior of School Children Based on Nutritional Status - Purnama, Ni Luh Agustini; Teju, Selly Omega Dila; Wahyuni, Lusia Dwi Sri (Babali Nursing Research, 2025)
Introduction: School-age children begin to develop eating behaviors that are independent of parents. Children have the freedom to do activities outside more signs of parental supervision and often eat unhealthy foods such as sweet snacks or light meals. The problem of school children's nutrition is a double burden, in addition to the problem of malnutrition at the same time the problem of overnutrition is increasing. The purpose of this study was to identify differences in eating behavior of school children based on nutritional status. Methods: The research design used was comparative. The research subjects were 137 students at elementary school of Pagerwojo Buduran Sidoarjo who met the inclusion criteria. Eating behavior was measured using the Children's Eating Behavior Questionnaire (CEBQ). Children's nutritional status was assessed based on the weight-for-height indicator (BW/TB) compared to the Z-score standard. Results: The results showed that 71.5% of school-age children had a tendency of eating behavior   food approach. A total of 59.9% were in normal nutritional (Z-score IMT/U).  The mean value in the food avoidance dimension shows the highest value in thinness and the lowest value in obese. Kruskal-Wallis test showed that there was a difference in the average score of approach behavior between the four categories of children's nutritional status (p=0.027). There is a difference in the average score of food aviodance behavior between the four categories of children's nutritional status (0.007). Conclusion: There are differences in eating behavior in children with undernutrition, good nutrition, overnutrition and obesity.